ARCHAEOLOGICAL RESEARCH ON BOTAI SETTLEMENT IN 2020 - Abilmalikov, K.K.; Serzhan-Abdrakhmanova, Sh K. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2020)
The article discusses the archaeological finds discovered during the Botay Archaeological expedition in 2020. The main goal of the Botay Archaeological expedition was to find a burial ground where the ancient inhabitants of the Botay culture could bury their dead. During 40 years of international research, no mass graves have yet been found on the Botay settlement and other settlements of the Botay Culture. And it remains a mystery where and how the ancient Botay people buried their dead. The Botay culture is known for the first evidence of the domestication of the steppe horse and the construction of multi-faceted rounded dwellings. The authors highlight the results of the Botay Archaeological expedition in 2020, the main goal of which was to search for burial grounds and burials to solve important scientific problems.
Keywords: Botay; archeology; excavations; Eneolithic; burial; burial ground